Effectiveness of commercial anti-graffiti treatments in two granites of different texture and mineralogy - Pozo-Antonio, JS; Rivas, T; Jacobs, RMJ; Viles, HA; Carmona-Quiroga, PM (Elsevier, 2018)
This paper presents a study of the efficiency of two chemically different anti-graffiti coatings (sacrificial and permanent anti-graffiti products) on two different compositional and textural granitic stones, Rosa Porriño and Albero. First, both uncoated and coated surfaces of the granites were characterized using stereomicroscopy and scanning electron microscopy, static contact angle measurements, colour spectrophotometry and gloss measurements. Results showed that both anti-graffiti products increased the static contact angle of the surfaces. The permanent anti-graffiti made them water-repellent without causing notable colour changes. Second, effectiveness of the anti-graffiti products was evaluated by means of the removal of two different spray graffiti paints (blue and silver colours) on both granites protected with the above-mentioned anti-graffiti products. The cleaning procedures were those recommended by the manufacturers. Fourier Transform Infrared spectroscopy and the previously mentioned techniques were used to assess the cleaning efficiency of the coated surfaces by detecting or not the presence of graffiti remains. As a result, textural differences in the granites, chemical composition of the graffiti paints and removal time were found to be the key parameters controlling the effectiveness of graffiti removal. On Albero granite, more residues of paint were found in its fissure system. Blue graffiti based on alkyd and polyester resins was more readily removed than silver paint. In general terms, graffiti extraction was more effective 30 days after painting than 3 days after.